2019
DOI: 10.1093/ije/dyz053
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-glucose index as a measure of insulin resistance and risk of obesity-related cancers

Abstract: Background The role of insulin resistance as a mediator in the association of body mass index (BMI) with site-specific cancer risk has, to our knowledge, never been systematically quantified. Methods Altogether 510 471 individuals from six European cohorts, with a mean age of 43.1 years, were included. We used the triglyceride glucose product (TyG index) as a surrogate measure for insulin resistance. We fitted Cox models, adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 40 publications
4
64
3
Order By: Relevance
“…The authors repeated the mediation analysis separately for the two biomarker groups, assuming that the pathways were independent. Although the HPFS included more inflammatory biomarkers compared with ours, similar to our results, the observed indirect effect through inflammation was small (OR NIE 40 . The strength of the mediating effect was similar in men and women, and after excluding participants who did not have diabetes 40 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The authors repeated the mediation analysis separately for the two biomarker groups, assuming that the pathways were independent. Although the HPFS included more inflammatory biomarkers compared with ours, similar to our results, the observed indirect effect through inflammation was small (OR NIE 40 . The strength of the mediating effect was similar in men and women, and after excluding participants who did not have diabetes 40 .…”
Section: Discussionsupporting
confidence: 88%
“…Although the HPFS included more inflammatory biomarkers compared with ours, similar to our results, the observed indirect effect through inflammation was small (OR NIE 40 . The strength of the mediating effect was similar in men and women, and after excluding participants who did not have diabetes 40 . In our study, we did not observe any mediating effect through HbA1c.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One plausible molecular mechanism for obesity-associated carcinogenesis is the chronic inflammatory state, which is the result of the activity of the visceral adipose tissue leading to the release of inflammatory cytokines and mediators [79]. Moreover, insulin resistance plays a promoting role in the pathogenesis of GI cancers [80].…”
Section: Gi Cancermentioning
confidence: 99%
“…The mechanism of TyG in T2DM is not clear, and several studies have provided clues to unpack the underlying mechanisms. First, previous studies demonstrated that TyG might have strong predictive ability for IR [41,42]. TyG has better predictive performance of IR than homeostatic model assessment (HOMA) in the Brazilian population [43].…”
Section: Discussionmentioning
confidence: 99%